Efeito do déficit hídrico temporário no solo sobre o crescimento de girassol e plantas daninhas em competição - Soares, Murilo Meira (Universidade Federal Rural do Semi-Árido, 2018)
The sunflower is among the most important and oil-bearing and water deficit tolerant can be grown in different regions of the world. However, bioactive factors such as the plants present in the cultivated areas, can intensify the effects of the water in the soil, affecting the growth of the crop. one of the world's leading oilseeds, tolerant of temporary water deficit in the soil. However, competition with weeds can change tolerance and reduce the effects of water deficit, such as reduced growth. Considering the above, the present work was evaluated as the difference between the soil and the weeds Amaranth and prickly pear and Waltheria indica and it makes water deficit without soil on the growth components of these species. The experiment was carried out in a greenhouse, in a randomized block design, with four replications. Data were organized in a 5x2 factorial scheme, with the first sign corresponding to the arrangements between the plants (sunflower + A. spinosus, sunflower + W. indica, sunflower, A. spinosus and W. indica in monoculture), and the second to water regimes . (irrigated and water deficit). The evaluated samples were: plant height, leaf area, leaf dry mass, stem, root and total. A chance between the growth plants of sunflower, W. indica and A. spinosus. The species W. indica and A. spinosus in convivence with sunflower plants aggravated the negative effects of water deficit under crop growth. A. spinosus exerts greater competition for water on the sunflower than a W. indica.
Monografia
Keywords: Helianthus annuus; Amaranthus spinosus; Waltheria indica; Déficit hídrico; Helianthus annuus; Amaranthus spinosus; Waltheria indica; Water deficit; CIENCIAS AGRARIAS::AGRONOMIA